A Real Living Contact with the Things Themselves. - Scalbert, Irénée (Zurich : Park Books, 2018)
Yokohama International Airport, Leicester Engineering Building, Rococo architectuur, The Economist Building, Alison and Peter Smithson, Bramante, St.John Caruso, New Art Gallery Walsall, Gotiek
Architectuurkritiek
boek